PELATIHAN TEKNIS PEMBUATAN PERANGKAT SISTEM IRIGASI SPRINKLER PIPA BERLUBANG UNTUK IRIGASI DI LAHAN - K. H. Iskandar; Fatria Resti Haryani; Primayoga Harsana Setyaaji; R. Mursidi; Haisen Hower; Hersyamsi Hersyamsi; Hilda Agustina; Ari Hayati (Universitas Pattimura, 2026)
This community service program was implemented in Payakabung Village, Ogan Ilir Regency, South Sumatra. In this village, the development of oil palm plantations is relatively slow because the majority of farmers still cultivate rubber and vegetables. In addition, oil palm cultivation is hampered by the need for large areas of land, a large water supply, and limited farmer knowledge regarding nurseries and irrigation technology. Therefore, this community service program was carried out with the aim of accelerating the transfer of knowledge and practical skills to farmers in Payakabung Village, especially in the adoption of simple and inexpensive irrigation technology for oil palm nurseries. The activity methods included site surveys, training, and evaluation of results involving 16 participants (village officials, farmers, and housewives). The evaluation results showed an increase in participant knowledge of 100%, pipe making skills of 87.5% and assembly/operation skills of 81.25% with 75% of achievement indicator components exceeding the target. The resulting activity outputs were perforated pipe sprinkler irrigation devices and video documentation. As a follow-up to support farmer income, this program recommends planning mini workshops on irrigation services, oil palm nursery training, and the provision of larger land areas.